2010
DOI: 10.1111/j.1538-7836.2009.03685.x
|View full text |Cite
|
Sign up to set email alerts
|

Can oral vitamin K before elective surgery substitute for preoperative heparin bridging in patients on vitamin K antagonists?

Abstract: This issue, pp 496-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…A recent small trial found that low-dose oral vitamin K, when given at noon on the day before surgery, failed to achieve adequate INR correction in Ͼ60% of patients who had discontinued their vitamin K antagonist 2 days before elective surgery; most of these patients were using fluindione or acenocoumarol (vitamin K antagonists not available in the United States). 5 A 12 There is moderate-quality evidence to support this recommendation; several studies indicate that a large proportion of patients with extreme INR elevation (eg, Ͼ10) will have their INR return to a safer range within 24 hours after 2 to 5 mg of oral vitamin K is administered. 13,14 Although some clinicians express concern that active anticoagulant reversal may place a patient with a prosthetic heart valve at high risk for thrombotic complications, we have conducted a small study that suggests low-dose oral vitamin K can be used in such patients without a high risk of overcorrection.…”
Section: -Year-old Man Is Hospitalized With Choledocholithiasis Andmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent small trial found that low-dose oral vitamin K, when given at noon on the day before surgery, failed to achieve adequate INR correction in Ͼ60% of patients who had discontinued their vitamin K antagonist 2 days before elective surgery; most of these patients were using fluindione or acenocoumarol (vitamin K antagonists not available in the United States). 5 A 12 There is moderate-quality evidence to support this recommendation; several studies indicate that a large proportion of patients with extreme INR elevation (eg, Ͼ10) will have their INR return to a safer range within 24 hours after 2 to 5 mg of oral vitamin K is administered. 13,14 Although some clinicians express concern that active anticoagulant reversal may place a patient with a prosthetic heart valve at high risk for thrombotic complications, we have conducted a small study that suggests low-dose oral vitamin K can be used in such patients without a high risk of overcorrection.…”
Section: -Year-old Man Is Hospitalized With Choledocholithiasis Andmentioning
confidence: 99%
“…Advanced age, decompensated heart failure, low weekly warfarin dose, and active malignancy are independent predictors of slow INR decay 4 ; patients with these characteristics or clinical features to suggest a higher-than-average bleeding risk may benefit the most from a more rapid INR correction because they may be exposed to a higher risk of bleeding. 5 Although the patient is asymptomatic, the treating physician decides to administer vitamin K. What dose and route of administration should be used?…”
Section: Ase Presentation: a 74-year-old Woman Presents To The Emermentioning
confidence: 99%
“…23 In a prospective, randomized trial, authors compared withholding warfarin beginning on day Ϫ5 before surgery with withholding warfarin beginning on day Ϫ2 before surgery and administering 1 mg of vitamin K on day Ϫ1. 24 For patients in whom warfarin was withheld beginning on day Ϫ5, the mean INR on the day of surgery was 1.24 (95% CI 1.19-1.29), but for patients in whom warfarin was withheld beginning on day Ϫ2, the mean INR was 1.61 (95% CI 1.50-1.71). 24 There are no randomized trials in which investigators have compared the effects of withholding warfarin for 5 days before surgery with the withholding of warfarin for Ͻ 5 days on perioperative bleeding outcomes.…”
Section: Interruption Of Vitamin K Antagonist Before Surgerymentioning
confidence: 99%
“…24 For patients in whom warfarin was withheld beginning on day Ϫ5, the mean INR on the day of surgery was 1.24 (95% CI 1.19-1.29), but for patients in whom warfarin was withheld beginning on day Ϫ2, the mean INR was 1.61 (95% CI 1.50-1.71). 24 There are no randomized trials in which investigators have compared the effects of withholding warfarin for 5 days before surgery with the withholding of warfarin for Ͻ 5 days on perioperative bleeding outcomes. 1 The elimination half-lives of vitamin K antagonists other than warfarin differ, with acenocoumarol having a shorter elimination half-life (10 hours) and phenprocoumon a longer elimination half-life (3-5 days).…”
Section: Interruption Of Vitamin K Antagonist Before Surgerymentioning
confidence: 99%
“…22 Further, in a randomized trial in which patients stopped warfarin 5 days or 1 day before surgery (the latter group also received 1 mg of vitamin K), the mean INR at surgery in the 5-day interruption group was 1.2. 23 Finally, the 5-day warfarin interruption period corresponds to approximately 2 half-lives of factor II, allowing time for this pivotal factor to be sufficiently replenished. 21 Resuming warfarin after surgery is feasible and safe for most patients on the evening of or the morning after surgery.…”
Section: If Warfarin Interruption Is Required When Should It Be Stopmentioning
confidence: 99%